2016
DOI: 10.1080/08923973.2016.1203929
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NF-κB and p38 MAPK pathways by scopoletin reduce the inflammation caused by carrageenan in the mouse model of pleurisy

Abstract: Natural products have long been used worldwide as therapeutic agents, but it is only recently, in response to the new challenges posed by global population aging, that interest in research into potentially therapeutic natural products has reemerged. In this context, coumarins, chemical compounds found in plants that have known anti-inflammatory activity, are promising candidates for the development of new drugs. In this study we test the effect of scopoletin, a coumarin found in several plant species, on carra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Cinnamaldehyde is found in both of our artichoke extracts, and it was shown by others to ameliorate the induced cardiac dysfunction in rats by inhibiting ROS production and autophagy through TLR4-NOX4 pathway and exhibits anti-inflammatory activity [32]. Similarly to others [33], we were able to identify the scopoletin in artichoke leaves hydro-alcoholic extracts, and it was suggested to have an important anti-inflammatory activity by inhibiting the phosphorylation of NF-κB and p38 MAPK in mice [34].…”
Section: Resultssupporting
confidence: 76%
“…Cinnamaldehyde is found in both of our artichoke extracts, and it was shown by others to ameliorate the induced cardiac dysfunction in rats by inhibiting ROS production and autophagy through TLR4-NOX4 pathway and exhibits anti-inflammatory activity [32]. Similarly to others [33], we were able to identify the scopoletin in artichoke leaves hydro-alcoholic extracts, and it was suggested to have an important anti-inflammatory activity by inhibiting the phosphorylation of NF-κB and p38 MAPK in mice [34].…”
Section: Resultssupporting
confidence: 76%
“…A proposed anti-inflammatory mechanism for oleanolic acid involves the upregulation of the transcription factor Nrf2, which inhibits the expression of NF-κB [42]. As oleanolic acid, the scopoletin anti-inflammatory effect also involves the inhibition of the NF-κB and p38 MAPK pathways [57]. Congruent with oleanolic acid and scopoletin anti-NF-κB activity, here, we demonstrate that the MpHE decreases the NF-κB activation in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…These plants produce scopoletin with different amount and can reach 700 nmol/g of fresh weight of the plant [4]. Following some reports on the traditional use of these plants, many studies have revealed that scopoletin exhibits some interesting pharmacological properties, ranging from anti-infectious, cytotoxicity, antiinflammatory, and those acting within the cardiovascular system [4][5][6][7][8]. In addition, some in vitro studies prove that scopoletin exhibits a potent antioxidant activity that makes this chemical even more potential for drug development [9][10][11].…”
Section: Introductionmentioning
confidence: 99%